## Yes, the formula for factoring the sum of two cubes is:

a^3 + b^3 = (a + b)(a^2 - ab + b^2).

In this case, we have (2xy^2)^3 + 3^3, which can be simplified using the formula to:

(2xy^2 + 3)((2xy^2)^2 - (2xy^2)(3) + (3)^2).

Now, let's simplify each term step by step:

(2xy^2)^2 = (2xy^2)(2xy^2) = 4x^2y^4.

(2xy^2)(3) = 6xy^2.

Substituting these values into the expression:

(2xy^2 + 3)(4x^2y^4 - 6xy^2 + 9).

And that is the simplified form of the expression (2xy^2 + 3)((2xy^2)^2 - (2xy^2)(3) + (3)^2).